PERSEPSI MASYARAKAT TERHADAP DAMPAK LINGKUNGAN PETERNAKAN AYAM PEDAGING (STUDI KASUS DI DUSUN JATILENGGER DESA JATILENGGER KECAMATAN PONGGOK KABUPATEN BLITAR) - Riyonaldi Dwia Juang Saputro; Edya Moelia Moeis; Risma Novela Esti (AVES: Jurnal Ilmu Peternakan, 2022)
Poultry farming, especially broilers, has good prospects and is growing rapidly. As the development of the livestock business will cause various impacts of waste which is a source of pollution. Therefore, it is necessary to examine thoroughly from an environmental and social perspective that involves the community. The purpose of this study was to determine the community's response to the presence of broiler farms. In the odor sub-variable the score obtained is 652 including in the disturbed category, in the waste sub-variable a score of 492 is included in the undisturbed category, the third sub-variable gets a score of 744 including the disturbed category and in the last sub-variable dust and feathers it gets a value of 444 This is included in the undisturbed category. people feel disturbed by the existence of broiler farms because of lack of cleanliness, causing public unrest. respondents are disturbed by the presence of a broiler farm which is approximately 50 meters from the house to the chicken coop.